2000
DOI: 10.1046/j.1439-0485.2000.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sponge Community of a Semi‐Submerged Mediterranean Cave

Abstract: Abstract. The sponge fauna of a semi‐submerged cave from the Tremiti Archipelago (Adriatic Sea) was studied, and its distribution was analyzed in relation to abiotic (water‐movement and light gradients) and biotic (algae and anthozoan substrate cover) ecological factors. Fifty‐five species of sponges were recorded. The number of species and the abundance values of sponges increase in the first part of the cave, then progressively decrease, with a sharp fall at the end of the cave. The quick disappearance of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 7 publications
(10 reference statements)
5
55
0
8
Order By: Relevance
“…This trend has been observed for many groups such as suspension and filter feeders (sponges, cnidarians, bryozoans and tunicates) (Bibiloni and Gili 1982;Gili et al 1986;Balduzzi et al 1989;Bibiloni et al 1989;Harmelin 1997;Benedetti-Cechi et al 1998;Corriero et al 2000;Bell 2002;Martí et al 2004a;Bussotti et al 2006), large decapods (Gili and Macpherson 1987), meiofauna (Todaro et al 2006), planktonic organisms (Garrabou and Flos 1995;Moscatello and Belmonte 2007), polychaetes (Denitto and Licciano 2006), fishes (Bussotti et al 2002(Bussotti et al , 2003; Bussotti and Guidetti 2009), etc. However, this trend has not been reported for the macro-infauna so far.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This trend has been observed for many groups such as suspension and filter feeders (sponges, cnidarians, bryozoans and tunicates) (Bibiloni and Gili 1982;Gili et al 1986;Balduzzi et al 1989;Bibiloni et al 1989;Harmelin 1997;Benedetti-Cechi et al 1998;Corriero et al 2000;Bell 2002;Martí et al 2004a;Bussotti et al 2006), large decapods (Gili and Macpherson 1987), meiofauna (Todaro et al 2006), planktonic organisms (Garrabou and Flos 1995;Moscatello and Belmonte 2007), polychaetes (Denitto and Licciano 2006), fishes (Bussotti et al 2002(Bussotti et al , 2003; Bussotti and Guidetti 2009), etc. However, this trend has not been reported for the macro-infauna so far.…”
Section: Discussionmentioning
confidence: 73%
“…The studies on hard-bottom assemblages suggest the processes determining spatiotemporal distribution patterns in marine caves to be highly complex, being context and scale dependent (BenedettiCechi et al 1998;Bussotti et al 2006). Thus, many other factors have been proposed to explain the distribution patterns observed (always for hard-bottom communities): physico-chemical gradients with respect to salinity, temperature, density and dissolved oxygen (Gili et al 1986;Zabala et al 1989;Harmelin 1997), diffusion-sedimentation processes (Garrabou and Flos 1995), the persistence of microlayer gradients along the walls (Gili et al 1986), variation in larval settlement and post-settlement events (Benedetti-Cechi et al 1996;Harmelin 1997;Denitto et al 2007), biotic interactions between species (Benedetti-Cechi et al 1996;Martí et al 2004bMartí et al , 2005Turon et al 2009), presence of hydrothermal springs (Benedetti-Cechi et al 1996, 1998, the depth and the exposure of the entrance (Corriero et al 2000;Bell 2002), differences in internal topography (Martí et al 2004a, b) and presence or absence of secondary openings (Zabala et al 1989). One of the main explications for the distribution of crustacean softbottom communities in the present study could be grain size.…”
Section: Discussionmentioning
confidence: 99%
“…Total species richness was comparable to Choi and Ginsburg (1983) who found 80 different species beneath coral rubble in Florida sand channels. Corriero et al (2000) found much lower species richness in Mediterranean caves, but richness inside was much higher than outside caves. Wunsch et al (2000) found in the Gulf of Aqaba much higher species richness compared to our Curaçao data set, probably due to much larger size of the cavities they studied.…”
Section: Community Composition and Diversitymentioning
confidence: 77%
“…Comparison with other quantitative studies conducted on the hard bottom fauna of similar structures in other marine ecosystems (including Adriatic Sea) are difficult, because the available data in the literature refer to studies on only few selected phyla or to short observation periods in the year [29,30,[40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%